Trichoderma species fungemia after high‐dose chemotherapy and autologous stem cell transplantation: a case report. Issue 4 (11th June 2014) - Festuccia, M.; Giaccone, L.; Gay, F.; Brunello, L.; Maffini, E.; Ferrando, F.; Talamo, E.; Boccadoro, M.; Serra, R.; Barbui, A.; Bruno, B.
Abstract We present a case of Trichoderma fungemia with pulmonary involvement in a multiple myeloma patient, who was severely immunocompromised and heavily treated with high‐dose melphalan, and underwent autologous hematopoietic cell transplantation. This is the first report, to our knowledge, of proven Trichoderma fungemia, defined by published criteria, successfully treated with voriconazole.